Sens, competences and materialities: self-care practice in informal caregivers in Valparaíso, Chile - Cazorla Becerra, Ketty (2024)
Introduction: The current social organization of care places women as its main responsible, especially in the case of informal care of dependents due to disability, being possible to assert that there is a tendency to devalue this work, especially in relation to the care of the caregiver. Objective: The article aims to describe the meanings, competencies and materialities that shape the practice of self-care in informal women caregivers. Method: Ostense in an interpretative epistemological perspective of exploratory-descriptive type and narrative qualitative method, 15 active interviews were conducted with informal caregivers of dependent people. Results: The results indicate that the possibilities for self-care practice are scarce and complex. However, when possible, it has three central features. In the first place, it is meant as an activity that contributes mainly to improving the quality of care of another, and not as an autonomous practice for the caregiver. Secondly, competences before and after the start of care work are resignified and transferred. And, thirdly, it uses both physical and digital support materialities. Conclusions: It is concluded that self-care is a practice that is built in an assembly of complex conditions that should not only be agency by the caregiver, but also involve her family, community, private and public environment.